Are Current Indonesian Math Materials Geared for the 21st Century? An Evaluation of 3rd Grade Content for Developing Critical Thinking Skills - Lestari, Shindy; Hermansyah, Agus Kichi; Trisnani, Novy (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
This paper investigates the development of critical thinking skills in Indonesian mathematics learning, which focuses on the analysis of the 2013 curriculum revised in 2018. The objective is to assess how well current mathematics materials for 3rd-grade elementary students promote 21st-century skills, especially for the 4C skills, namely critical thinking and problem solving, communication, collaboration, creativity, and innovation. The research highlights the necessity of innovative approaches in teaching mathematics to enhance these skills. The analysis indicates that the mathematics content in the thematic books supports the development of 4C skills. Additionally, the researcher suggested implementing Realistic Mathematics Education (RME) as an effective innovation and aligning RME's characteristics with the required 4C skills to better prepare students for 21st-century challenges. While Indonesia's low PISA scores in mathematics underscore the need for improvement. The study in this paper provides insights into curriculum enhancements that can lead to better educational outcomes.